Iran in the Minds of the Israe - Levy, Mordechai (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2015)
The foreign policy of Israel towards Iran relies on the shared understanding of the leadership and the public in Israel of the reality, and hence agreement is also built regarding the steps that should be undertaken regarding Iran and its nuclear program. Through research of the social representations, it will be possible to identify the core images and bases of agreement of society in Israel and to identify the existence of alternative understanding of subgroups, which exist in parallel in the society. The findings indicate that the heterogeneity in Israeli society is expressed also in the collection of images and explanations regarding the nature of the State of Israel and re¬garding the Iranian threat. In the Jewish group it is possible to identify two systems of core repre¬sentations: the first is collection of images of the Holocaust and the second is images of the Israeli-Arab conflict. In the Arab group differences among its sub-groups was found. Groups whose sons serve in the Israeli military created discourse similar to the Jewish group, and the other Arabs formed images around the status as a minority in the Jewish nation state.

Polityka zagraniczna Izraela wobec Iranu opiera się na założeniu, że Iran stanowi zagrożenie dla bezpieczeństwa także ze względu na program atomowy. W ramach badań nad społeczną reprezentacją w Izraelu, postrzeganie Iranu jest różne tak, jak heterogeniczne jest społeczeństwo izraelskie. W ustaleniach badawczych w grupie żydowskiej można wyróżnić dwa podstawowe czynniki wpływające na postrzeganie zagrożenia ze strony Iranu. Są nimi doświadczenie Holocaustu oraz konfliktów arabsko-izraelskich. W grupie arabskich mieszkańców Izraela występują poważniejsze różnice w postrzeganiu Iranu. W pierwszej podgrupie, w której synowie służą w armii izraelskiej występuje dyskurs podobny do grupy żydowskiej, natomiast w drugiej wyobrażenia o Iranie uformowane zostały z perspektywy mniejszości znajdującej się w żydowskim państwie narodowym.
Iran w pojmowaniu Izraelczyków